PRODUCT DEVELOPMENT OF MANGOSTEEN PEEL SYRUP PROCESSING, (MSMES) INDONESIA, BOGOR REGENCY - Bayu Purnama Putra; Ermi Suryani Harahap; Adilah Rahma Pulungan (Proceeding International Seminar of Islamic Studies, 2022)
Mangosteen peel can be processing into syrup to immunity increasing and prevent many diseases suffered by the people of Indonesia and abroad. Empowerment of (MSMEs) Indonesian Farmer Groups enterpreneur (FGE), Karacak Village, Cengal Bogor Regency is doing by maximizing guidance and assistance by Stakeholders of Micro, Small and Medium Enterprises (MSMEs) as ongoing to MSMEs facilitate as financially and non-financially. The biggest obstacles are the initial capital as wages for the early stage workers of UMKM, the cost of administering the BPOM and the Halal label. Accordancing with capital business theories is not the end of the business running but it is only part of the smoothly roadblocks. Therefore, Indonesian MSMEs will be continue product quality developing, wider marketing, strengthening of human resources and administration completing to be bigger from home made into a big industry. The new product of Indonesian MSMEs developed by UMKM is syrup (Health Mangosteen Syrup). The difference between Health Mangosteen Syrup with Marjan Syrup and ABC Syrup is the raw materials higher in dosage and non preservative. The Self life of Health Mangosteen Syrup products is doing by traditional trials for one year. In addition to immunity increasing, Health Mangosteen Syrup has the function are weight losing, controlling of blood sugar levels, skin health maintaining, cancer disease preventive, relieving of arthritis, heart health, brain, mental health, and digestive health maintaining. This product is deserves to into the national and international market because it is part of human needs.Keywords: Health Mangosteen Syrup, Quality Product, Marketing Strategy